When phylogeny meets geology and chemistry: doubts on the dating of Ethiopian amber. Issue 3 (3rd May 2016) - Coty, David; Lebon, Matthieu; Nel, André
Summary: The first fossil species of a Melissotarsus ant is described ( Melissotarsus ethiopiensis n. sp. ), suggesting that Ethiopian amber could be cenozoic rather than cretaceous. This hypothesis is supported by a Fourier transform infrared spectroscopy (FTIR) analysis of the amber itself, suggesting a weak maturation of the fossil resin, and a revision of the pyrolysis–gas chromatography–mass spectrometry (PY-GC-MS) analysis done by Schmidt and his collaborators in 2010, in an article in which the deposit was described for the first time.